Tribological and rheological properties of the ultrafine CaCO3 blended nano grease. Issue 3 (28th February 2022) - Akhtar, Khalida; Yousafzai, Saniya
Abstract: Calcium carbonate uniform nanoparticles of the tailored morphologies were produced under a narrow set of experimental parameters. The as-synthesized CaCO3 particles of novel morphologies were used as lubricant additives in commercial grease and the effect of these additives on the tribological properties of the commercial Lithium greases (CLG) was studied by the four-ball tribometer. The grease blended with commercially available CaCO3 powder was also analyzed under the same conditions for comparison study. Results showed that the as-prepared monodispersed CaCO3 particles considerably improved the tribological properties of the CLG as compared to the irregular particles of the commercial calcium carbonate. The grease blends showed the best results at the optimum amount of 3 weight % of the added CaCO3 oval and rod shape particles. Among the as-synthesized ultrafine calcium carbonate particle systems, oval shape particles exhibited more improvement in the anti-wear performance than rod shape particles. Preliminary experiments regarding the rheological study of the grease blends showed a decrease in the shear stress as compared to their blank partners. The oval calcium carbonate particles showed the lowest values of the shear stress at any shear rate as compared to the rod and commercial CaCO3 particles. Furthermore, the anti-wear/friction and rheological properties of the greases were enhanced in the order of Momin > Awami > Sinopec by blending with the as-synthesized CaCO3 particles. GRAPHICAL ABSTRACT: UF0001